2022
DOI: 10.3390/genes13081359
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposon Insertion Polymorphisms (RIPs) in Pig Reproductive Candidate Genes

Abstract: Retrotransposons account for more than one-third of the pig reference genome. On account of the genome variability in different breeds, structural variation (SV) caused by retrotransposon-generated deletion or insertion may have a function in the genome. Litter size is one of the most important reproductive traits and significantly impacts profitability in terms of pig production. We used the method of bioinformatics, genetics, and molecular biology to make an analysis among different pig genomes. Predicted 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…It has been reported that FSH β short interspersed nuclear elements (SINEs) and 212T>C both affect pig LS [24]. The PRLR SINE also affects pig LS [29]. Another study reported that GDF9 affects swine LS and identified 12 SNPs, of which 3 are associated with LS [27].…”
Section: Candidate Genes Affect Swine Lsmentioning
confidence: 99%
“…It has been reported that FSH β short interspersed nuclear elements (SINEs) and 212T>C both affect pig LS [24]. The PRLR SINE also affects pig LS [29]. Another study reported that GDF9 affects swine LS and identified 12 SNPs, of which 3 are associated with LS [27].…”
Section: Candidate Genes Affect Swine Lsmentioning
confidence: 99%
“…Despite the potential advantages of TEs, many insertions result in a disease state, or even a lethal allele. For instance, the SINE insertion in IDO2 had a negative impact on the reproductive traits of litter birth-weight, which was significantly (p < 0.05) affected in the Large White pig breed [13]. A recent study on the swamp buffalo (Bubalus bubalis) [14] reported that the 2809-bp-long LINE-1 insertion in the agouti signaling protein (ASIP) gene is the causative mutation for the white coat phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Retrotransposon can be classified into long terminal repeat (LTR) elements, which mainly contain endogenous retrovirus (ERV) and non-LTR elements (Long interspersed nuclear elements, LINEs; Short interspersed nuclear elements, SINEs). Retrotransposons contribute to genetic diversity [22][23][24] and generate rich polymorphism [25][26][27] in the mammal genome. By changing gene expression patterns, retrotransposon insertion can result in human neurologic and psychiatric disorders [28][29][30], genetic disorders [31,32], and cancer [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…RIPs were utilized to evaluate the genetic variation and population structure of different pig breeds [41,42]. Additionally, RIPs in important protein-coding genes were conducted to determine their association with porcine phenotypes, including coat color [43], reproductive traits [25,44], growth traits [45,46], and immunity [47]. Based on the genetic variation and population structure evaluations conducted in previous studies, as well as the importance of PPARs in lipid metabolism, RIPs in these genes were identified in this study.…”
Section: Introductionmentioning
confidence: 99%